Music Teacher Dispositions: Self-Appraisals and Values of University Music Students. (April 2018) - Woody, Robert H.; Gilbert, Danni; Laird, Lynda A.
For music teachers to be most effective, they must possess the dispositions that best facilitate their students' learning. In this article, we present and discuss the findings of a study in which we sought to explore music majors' self-appraisals in and the extent to which they value the disposition areas of reflectivity, empathic caring, musical comprehensiveness, and musical learnability orientation. Evidence from a survey of 110 music majors suggested that music education students possess and value the dispositions of reflectivity, musical comprehensiveness, and musical learnability orientation more highly after they have matured through their college careers. Additionally, based on their responses to music teaching scenarios, it appears that senior music education majors possess greater empathic caring than do their freshman counterparts.